Factors affecting farmers' decision to harvest rainwater for maize production in Ghana - Bessah, Enoch; Donkor, Emmanuel; Raji, Abdulganiy O.; Taiwo, Olalekan J.; Ololade, Olusola O.; Strapasson, Alexandre; Amponsah, Shadrack K.; Agodzo, Sampson K. (Frontiers in Water, 2022)
Climate change, especially the variability of rainfall patterns, poses a threat to maize production in Ghana. Some farmers harvest rainwater and store for maize production to cope with unpredicted rainfall patterns. However, there are only a few studies on the adoption of rainwater harvesting for maize production. This study analyses the factors that influence farmers’ decision to harvest rainwater for maize production in Ghana. A probit regression model is applied for the empirical analysis, using primary data from 344 maize farmers. The results show that 38% of the farmers harvest rainwater. We find that male farmers, farmers with primary education, large-scale farmers, experienced farmers, and those with access to weather information are more likely to harvest rainwater, while older farmers, those with limited access to extension services and labour, and those who perceive changes in rainfall pattern and amount of rainfall are associated with a lower probability to harvest rainwater for maize production. The findings suggest that enhancing farmers’ access to weather information and extension services, improving awareness of climate change are needed to promote the adoption of rainwater harvesting. For gender inclusiveness in the adoption of rainwater harvesting, policies need to consider the needs of women.